Effects of Cl adatom on Na-Decorated graphene. (8th May 2015) - Song, Xinxiang; Sun, Yu; Dong, Meifeng; Li, Chun; Wang, Jiesheng; Mimura, Hidenori; Yuan, Guang
Abstract: The effects of the Cl adatom on Na-decorated graphene are studied using first principles density functional theory under the generalized gradient approximation to calculate the adsorption energy, geometric structure, charge density difference, and density of states. When Na and Cl adatoms are simultaneously absorbed on opposite sides of graphene, the adsorption energy of Na increases by about 1 eV and the adsorption system becomes more stable because graphene can effectively transfer the 3s valence of the Na adatom to the Cl adatom.